The Pengaruh Takaran Pupuk Nitrogen terhadap Serangan Penyakit Layu Fusarium dan Pertumbuhan pada Tanaman Pisang (Musa sp.) - Arifandi, Zulfahri; Chrisnawati, Chrisnawati; Meyuliana, Aulia; riska, riska; Jumjunidang, Jumjunidang (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
Fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense (Foc) is a major constraint in banana cultivation, and its development in the field is frequently associated with improper nitrogen fertilization. However, information on how different nitrogen fertilizer rates influence Fusarium wilt severity remains limited. This study aimed to evaluate the effect of varying nitrogen doses on Fusarium wilt and growth of banana. The experiment was conducted under laboratory and field conditions at the Horticulture Research Center of BRIN, Solok, Indonesia, using a randomized block design with nine treatments and four replications. The treatments were nitrogen with different rates (control, 100, 250, 400, and 550 kg ha⁻¹ year⁻¹), applied with and without Foc inoculation. The results demonstrated that nitrogen fertilization enhanced vegetative growth of banana plants under pathogen-free conditions. However, in Foc-infected plants, increasing nitrogen rates—particularly at high levels—exacerbated disease development. High nitrogen rates (400–550 kg ha⁻¹ year⁻¹) accelerated symptom appearance, indicated by shorter incubation periods, and increased disease severity. In contrast, a moderate nitrogen rate (250 kg ha⁻¹ year⁻¹) delayed symptom development and reduced disease severity, although it did not prevent infection. These findings suggest that excessive nitrogen fertilization increases Fusarium wilt severity, while moderate nitrogen application may help suppress disease progression. Therefore, nitrogen management in Fusarium wilt–endemic banana production areas should prioritize moderate nitrogen rates and avoid excessive fertilization as part of an integrated and sustainable disease management strategy.